2009
DOI: 10.1308/rcsann.2009.91.6.483
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-Term Outcomes of Patients Undergoing Liver Resection and Diaphragm Excision for Advanced Colorectal Liver Metastases

Abstract: Ann RC oll Surg Engl 2009; 91:4 83-488 483Colorectal carcinoma is common in the Western world. 1,2 Approximately 50% of patients diagnosed with the disease develop liver metastases. 3,4 Currently,f or patients with colorectal liver metastases, liver resection offers the only potential chance for cure. However,t he proportion of patients with colorectal liver metastasese ligible for liver resection remains low (20-30%), 5,6 although there has been asteady increase over the past 10-15 years, [1][2][3][4] largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…Currently, most institutions conduct a preoperative examination with CT and MRI, and these imaging modalities have been improved; nevertheless, it remains difficult to determine whether a hepatic tumor has invaded an adjacent organ or not. Previously, the rate of proven pathological invasions into adjacent organs associated with colorectal liver metastasis has ranged from 15 to 44% (8,24), and the rate of confirmed pathological invasions in this study was within that range. Previous studies have identified several indicators for supporting a preoperative diagnosis of invasion into an adjacent organs (24)(25)(26).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Currently, most institutions conduct a preoperative examination with CT and MRI, and these imaging modalities have been improved; nevertheless, it remains difficult to determine whether a hepatic tumor has invaded an adjacent organ or not. Previously, the rate of proven pathological invasions into adjacent organs associated with colorectal liver metastasis has ranged from 15 to 44% (8,24), and the rate of confirmed pathological invasions in this study was within that range. Previous studies have identified several indicators for supporting a preoperative diagnosis of invasion into an adjacent organs (24)(25)(26).…”
Section: Discussionsupporting
confidence: 64%
“…Around 2010, several authors reported that liver resections combined with a simultaneous diaphragm excision resulted in high morbidity (44%) but relative low mortality (3-7%) compared to a liver resection alone for advanced colorectal liver metastases (8,9). In contrast, conscerning about hepatectomy combined with a IVC resection, several studies reported high morbidity and mortality (40-43 and 8-11% respectively) (11,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopted a policy in 1996 of standard neo-adjuvant chemotherapy followed by liver surgery for synchronous and early (<2years) metachronous CRLM, and for late metachronous (>2years) CRLM who were considered to have potentially threatened resection margins on pre-operative imaging [20][21][22][23] . The aim of this study was to analyse the effects of width of resection margin as a predictor of outcome in this setting.…”
Section: Introductionmentioning
confidence: 99%